Application of K-Means Clustering Method in Determining Student Majors at SMA Negeri 6 Bengkulu Tengah Based on Student Subject Values Per Semester - Ikbal, Muhammad; Yupianti, Yupianti; Alinse , Rizka Tri (Jurnal Komputer Indonesia, 2022)
At SMA Negeri 6 Bengkulu Tengah the Department is divided into 2, namely science and social studies. Determination of majors in schools is done based on the value per subject obtained by students. However, the data processing process is still done manually, sometimes students can choose the desired majors themselves so that over time the student learning process looks bored because the majors chosen are not in accordance with what students expect. The clustering application of student subject values ​​per semester at SMA Negeri 6 Bengkulu Tengah is used to assist the school in managing student data, the value of student subjects so that the appropriate student majors are known based on the scores obtained by students. In grouping the student's subject value data in the application, the K-Means Clustering method has been applied so that it can produce 2, namely Cluster C1 (IPA) and Cluster C2 (IPS). The application for clustering student subject values ​​per semester at SMA Negeri 6 Bengkulu Tengah was made using the Visual Basic.Net programming language. Based on the results of the tests that have been carried out, the functional clustering application of student subject values ​​per semester at SMA Negeri 6 Bengkulu Tengah runs well as expected and can provide information on the results of clustering student data into 2 groups, namely science and social studies.